2018
DOI: 10.1038/s41598-018-26525-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as potential diagnostic biomarkers for osteoporosis

Abstract: Osteoporosis is the most common age-related bone disease worldwide and is usually clinically asymptomatic until the first fracture happens. MicroRNAs are critical molecular regulators in bone remodelling processes and are stabilised in the blood. The aim of this project was to identify circulatory microRNAs associated with osteoporosis using advanced PCR arrays initially and the identified differentially-expressed microRNAs were validated in clinical samples using RT-qPCR. A total of 161 participants were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
78
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 43 publications
5
78
2
Order By: Relevance
“…More recently, screening serum levels of 139 patients, which included controls, osteopenic (with and without fractures), and osteoporotic (with and without fracture), for the presence of circulating miRNAs, found miR122‐5p and miR‐4516 to be present at significantly different levels between nonosteoporotic control, osteopenic, and osteoporosis patients. Specifically, miR‐122‐5p levels were much lower in osteoporosis patients compared with nonosteoporotic control and osteopenic patients.…”
Section: Mirna Profiling and Fracturesmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, screening serum levels of 139 patients, which included controls, osteopenic (with and without fractures), and osteoporotic (with and without fracture), for the presence of circulating miRNAs, found miR122‐5p and miR‐4516 to be present at significantly different levels between nonosteoporotic control, osteopenic, and osteoporosis patients. Specifically, miR‐122‐5p levels were much lower in osteoporosis patients compared with nonosteoporotic control and osteopenic patients.…”
Section: Mirna Profiling and Fracturesmentioning
confidence: 99%
“…Moreover, the levels of miR‐4516 were significantly lower in osteoporotic patients with fracture compared with those without. The authors suggested that their results indicate that the decreasing levels of miR‐122‐5p and miR‐4516 in clinical samples might be associated with the development of osteoporosis …”
Section: Mirna Profiling and Fracturesmentioning
confidence: 99%
See 3 more Smart Citations